Perancangan Sistem Presensi Sekolah Berbasis Web Di SD Muhammadiyah Gresik - Roudhotum Mawardania; Henny Dwi Bhakti (Lembaga Pengembangan Kinerja Dosen, 2024)
Technological developments are occurring rapidly in various areas of human life where manual data processing is slowly being abandoned and society is starting to realize the importance of the role of computers. In the world of education there is also a need for a system that can help with data processing, almost everything now uses technology, both in processing student data and for other purposes. However, the Gresik Muhammadiyah Elementary School school still uses manual attendance, namely using student attendance attendance books so that sometimes errors occur which make reports inaccurate and less effective. This also often happens when searching for data storage documents, sometimes the book is lost or sometimes the archive book is damaged. Apart from that, parents can only see their child's attendance report when the report cards are distributed so that in the attendance process currently implemented it is difficult for parents to monitor whether their child is actually going to school or playing somewhere else without the school knowing. Therefore, an information system is needed that is able to reduce or even eliminate deficiencies that arise in the process of processing attendance data that occur at SD Muhammadiyah Gresik. The aim is to make it easier to manage student attendance, help teachers to fill in student attendance, and be able to produce student attendance reports more quickly and accurately so that errors can be minimized. This online web-based school attendance system was built using waterfall model software, PHP programming language and MySQL database. This system allows us to provide solutions to make participation easier to use, as well as effective and efficient